Generalization of Loo Keng-Hua’s lemma for an algebraic number fields - Kalinka, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Калинка. Обобщение одной леммы Хуа Ло-Кена для алгебраических чисел V. Kalinka. Vienos Hua Lo-Keno lemos apibendrinimas algebrinių skaičių kūne